2016
DOI: 10.1002/jbm.a.35764
|View full text |Cite
|
Sign up to set email alerts
|

Diphenylalanine peptide nanotubes self‐assembled on functionalized metal surfaces for potential application in drug‐eluting stent

Abstract: This study focuses on the potential of diphenylalanine self-assembled peptide nanotubes (FF Nts) for delivery of flufenamic acid (FA) from metal implants. Self-assembly of FF Nts was studied in solution and on surfaces of glass, silicone and gold substrates. FA was loaded inside the shell of FF Nts and subsequently FF/FA Nts were attached to gold surfaces. The substrate were characterized by Field Emission Scanning Electron Microscopy (FESEM), fluorescence microscopy, confocal microscopy, and UV-vis spectrosco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 49 publications
0
16
0
Order By: Relevance
“…The hydrophobic forces in these well-ordered tubular structures further facilitated to be soluble in a suitable solvent and self-assemble into well-organized films on various substrates. This technique was tried by Zohrabi et al (2016) wherein FFA loaded inside the H-Phe-Phe-OH nanotubes were coated onto Au surfaces functionalized with 3-mercaptopropionic acid (MPA). The biocompatibility and in vitro release studies confirmed the potential of H-Phe-Phe-OH nanotubes as an alternate system for polymer coating in drugs eluting stents.…”
Section: Dipeptides For Biologics Deliverymentioning
confidence: 99%
“…The hydrophobic forces in these well-ordered tubular structures further facilitated to be soluble in a suitable solvent and self-assemble into well-organized films on various substrates. This technique was tried by Zohrabi et al (2016) wherein FFA loaded inside the H-Phe-Phe-OH nanotubes were coated onto Au surfaces functionalized with 3-mercaptopropionic acid (MPA). The biocompatibility and in vitro release studies confirmed the potential of H-Phe-Phe-OH nanotubes as an alternate system for polymer coating in drugs eluting stents.…”
Section: Dipeptides For Biologics Deliverymentioning
confidence: 99%
“…The use of diphenylalanine for various technological applications has been repeatedly demonstrated (reviewed in 138). Such applications include providing energy for the locomotion of a nanoboat (140), production of electricity using a piezoelectric array of peptide nanorods (141) (Figure 2), coating of medical devices (142), and fabrication of a thermometer that measures low physiological temperatures (143) and those near absolute zero (144). For a list of some examples of technological applications and their references see Table 1.…”
Section: Diphenylalanine As a Key Building Blockmentioning
confidence: 99%
“…[6][7][8][9][10] FFNTs have also been explored for use in the biomedical field as biomimetic scaffolds, sensors, and drug delivery agents due to their relatively nontoxic properties. [11][12][13] Building on these advancements, current studies are looking at other possible protein-like NTs that can be formed from modified FF, [14] l/d amino acids, [15][16][17] and dipeptides from the combination of other aromatic amino acids tryptophan (W) and tyrosine (Y). [18][19][20][21][22] The crystal structure of FFNTs has been well elucidated, [23][24][25][26][27] involving stacks of hexameric rings of FF in a head-to-tail conformation for intramolecular hydrogen bonding.…”
Section: Introductionmentioning
confidence: 99%
“…The early works of Reches and Gazit reported hollow self‐assembled FFNTs exhibiting exceptional stability and resistance from mechanical and chemical strains (e. g., heat, solvents, and enzymes), [4,5] leading to the development of FFNT with remarkable properties such as semi‐conductor properties, photoluminescence, imaging, nanofluidics, and quantum dots, to cite a few [6–10] . FFNTs have also been explored for use in the biomedical field as biomimetic scaffolds, sensors, and drug delivery agents due to their relatively nontoxic properties [11–13] . Building on these advancements, current studies are looking at other possible protein‐like NTs that can be formed from modified FF, [14] l/d amino acids, [15–17] and dipeptides from the combination of other aromatic amino acids tryptophan (W) and tyrosine (Y) [18–22] …”
Section: Introductionmentioning
confidence: 99%